Knowledge, Spirit, Law, Book 2: The Anti-Capitalist Sublime - Keeney, Gavin (punctum books, 2017)
Knowledge, Spirit, Law // Book 2: The Anti-capitalist Sublime takes up where Knowledge, Spirit, Law // Book 1: Radical Scholarship (2015) left off, foremost in terms of a critique of neo-liberal academia and its demotion of the book in favor of various mediatic practices that substitute, arguably, for the one form of critical inquiry that might safeguard speculative intellectual inquiry as long-form and long-term project, especially in relationship to the archive or library (otherwise known as the "public domain"). This ongoing critique of neo-liberal academia is a necessary corrective to processes underway today toward the further marginalization of radical critique, with many of the traditional forms of sustained analysis being replaced by pseudo-empirical studies that abandon themes only presentable in the Arts and Humanities through the "arcanian closure" that the book as long-form inquisition represents (whether as novel, non-fictional critique, or something in-between). As a tomb for thought, this privileging of the shadowy recesses of the book preserves, through the very apparatuses of long- and slow-form scholarship, the premises presented here as indicative of an anti-capitalist project embedded in works that might otherwise shun such a characterization.